2013
DOI: 10.1177/0961203313497119
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of methyl-CpG-binding protein 2 and autoimmunity: evidence from MECP2 duplication syndrome, lupus, MECP2 transgenic and Mecp2 deficient mice

Abstract: Methyl-CpG-binding protein 2 (MeCP2) is a key transcriptional regulator that can induce either silencing or activation of target genes. Genetic polymorphisms in the MECP2/IRAK1 locus have been associated with increased susceptibility to multiple autoimmune diseases such as lupus, primary Sjogren's syndrome, and more recently rheumatoid arthritis. Data from our group suggest that the disease risk variant in this locus is associated with gain of MeCP2 function. Recent findings indicate that MECP2 duplication in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…However, Yang and colleagues identified immune defects among the patients with MECP2 DS had no association with IRAK1 duplication by transgenic mice that overexpressed MECP2 without IRAK1 duplication [ 21 ]. This conclusion was supported by Sawalha [ 22 ]. Chronic intestinal pseudo–obstruction (CIPO), thrombcytopaenia, patent ductus arteriosus (PDA), malrotation were found in two families with the duplications involved only the FLNA gene [ 23 ].…”
Section: Discussionsupporting
confidence: 67%
“…However, Yang and colleagues identified immune defects among the patients with MECP2 DS had no association with IRAK1 duplication by transgenic mice that overexpressed MECP2 without IRAK1 duplication [ 21 ]. This conclusion was supported by Sawalha [ 22 ]. Chronic intestinal pseudo–obstruction (CIPO), thrombcytopaenia, patent ductus arteriosus (PDA), malrotation were found in two families with the duplications involved only the FLNA gene [ 23 ].…”
Section: Discussionsupporting
confidence: 67%
“…Also, two proteins have been involved in regulating the immune response. Recent studies found that MeCP2 is important for the expression of sustained Foxp3 in Tregs during inflammation and was indispensable for the differentiation of naïve CD4 + T cells into Th1 and Th17 cells and for Th1 or Th17-mediated pathologies in vitro and in vivo ( 50 , 51 ). Furthermore, MeCP2 protein undergoes multiple SUMOylation and acetylation, which impact its functions ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cases with a duplicated region inclusive of IRAK1 with no history of respiratory infections have been reported [ 42 , 53 , 55 ], as has a female patient who had recurrent respiratory infections but not a duplicated IRAK1 region [ 43 ]. Mice models of MDS with an overexpression of human MECP2 without IRAK1 have also been shown to be immunodeficient suggesting that immune defects in MDS may likely be independent of IRAK1 duplication [ 126 , 127 ].…”
Section: The Syndromic Phenotype Of Mecp2 Duplicat...mentioning
confidence: 99%